Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
a) 5 1/3 * 1 1/2 - 6 : 4 2/3 = 16/3 * 3/2 - 6 : 14/3 = 48/6 - 6 * 3/14 =
8 - 18/14 = 8 - 1 2/7 = 6 5/7
b) 3 1/5 *(2 1/2 - 1 1/4 : 6) = 16/5 * (5/2 - 5/4 * 1/6) = 16/5 * (5/2 - 5/24) =
16/5 * (60/24 - 5/24) = 16/5 * 55/24 = (16*55)/(5*24) = (2*11)/(3) = 22/3= 7 1/3
c) 1 3/7 * (2 1/2 : 1 1/2 - 1 1/3 : 1 1/7) = 10/7 * (5/2 : 3/2 - 4/3 : 8/7) =
= 10/7 * (5/2 * 2/3 - 4/3 * 7/8) = 10/7 * (5/3 - 28/24) = 10/7 * (5/3 - 7/6) =
= 10/7 * (10/6 - 7/6) = 10/7 * 3/6 = 30/42 = 5/7
d) (5 4/7 - 1 2/7)/[3 1/3 * (1 1/4 - 1/2)] = (4 2/7)/[10/3 * (5/4 - 2/4)] =
= (30/7)/[10/3 * 3/4] = (30/7)/(10/4) = 30/7 : 10/4 = 30/7 * 4/10 =
= (30*4)/(7*10) = (3*4)/7 = 12/7 = 1 5/7